Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Maharashtra State Part II - Planning Commission (Planning Commission, 2002)
Tenth five year plan and Annual plan Abstract Statement Showing Sub-Sectorewise Outlay and Expenditure Abstract Statement Indicating outlay and Expendeture on Centrally Sponsored programmes Tribal Sub-Plan outlay and Expenditure Special Component Plan outlay and expenditure Head of Development outlay and expenditure 20-Point pragramme-outlay and expenditure Detail Statemet included in the Annual Plan 2002-03
Planning Department Government of Maharashtra